Business model design and learning a strategic guide - Spencer, Barbara. (2013 digital library., 2013)
The purpose of this book is to explain what a business model is, what you have to do to get one, and what to do about the one you've already got. It contends that to be successful, your business model must be focused sharply on your customer. And it argues that you must think strategically about how to use your business model if you want to gain an advantage over your competitors.